2019
DOI: 10.1093/ndt/gfz098
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality risk associated with serum sodium variations and borderline hypo- and hypernatremia in hospitalized adults

Abstract: Background This study aimed to evaluate short-term and long-term mortalities in a cohort of unselected hospitalized patients with serum sodium concentration ([Na+]) variations within and outside of reference range. Methods All adult patients admitted to the Mayo Clinic, Rochester, MN, USA from January 2011 to December 2013 (n = 147358) were retrospectively screened. Unique patients admitted during the study period were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…We tested the difference in clinical characteristics among discharge sodium groups using ANOVA for continuous variables and the Chi-square test for categorical variables. We categorized discharge serum sodium into five groups; ≤132, 133-137, 138-142, 143-147, and ≥148 mEq/L, as previously described in literature, [14][15][16] What's known?…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We tested the difference in clinical characteristics among discharge sodium groups using ANOVA for continuous variables and the Chi-square test for categorical variables. We categorized discharge serum sodium into five groups; ≤132, 133-137, 138-142, 143-147, and ≥148 mEq/L, as previously described in literature, [14][15][16] What's known?…”
Section: Discussionmentioning
confidence: 99%
“…The association between dysnatremia and increased short and long-term mortality was previously reported by several investigators. 5,9,14,15,17 Both decrease and increase in discharge serum sodium from the optimal range were associated with increased 1-year mortality, as shown in the U-shape mortality curve. We observed that any degree of deviation of discharge serum sodium from the optimal range was associated with increased 1-year mortality, even if the deviation was minimal.…”
Section: Ta B L Ementioning
confidence: 94%
See 3 more Smart Citations